UMPSA Vice-Chancellor’s caring visit brings hope to the daughter of Cendol Cartoonist, Arysha Rania - Naqiah, Puaad (UMPSA, 2025)
SHAH ALAM, 15 July 2025 – “I am truly grateful and happy. This is a blessing that came through my daughter’s opportunity to study at the university of her choice,” said Shahrul Nizam, better known as Cendol Cartoonist, during a special visit from the Vice-Chancellor of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), Professor Dr. Yatimah Alias, accompanied by Datin Nur Sharmila Shaheen, Member of the Board of Trustees of the UMPSA Foundation.